2017
DOI: 10.1021/acs.nanolett.6b04523
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Microcapsule-Mediated Targeted Delivery of Diverse Nanoparticles for Imaging and Therapy via the Oral Route

Abstract: Targeting of nanoparticles to distant diseased sites after oral delivery remains highly challenging due to the existence of many biological barriers in the gastrointestinal tract. Here we report targeted oral delivery of diverse nanoparticles in multiple disease models, via a "Trojan horse" strategy based on a bioinspired yeast capsule (YC). Diverse charged nanoprobes including quantum dots (QDs), iron oxide nanoparticles (IONPs), and assembled organic fluorescent nanoparticles can be effectively loaded into Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
96
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(109 citation statements)
references
References 41 publications
9
96
0
Order By: Relevance
“…[13,14] A recent study revealed the potential of Ac2-26 for the treatment of colitis after intraperitoneal or intramucosal injection of Ac2-26 in nanoparticles (NPs). [16][17][18][19][20][21] However, there are still tremendous challenges in the design and development of translational nanovehicles for oral delivery of macromolecular therapeutics, [16,[22][23][24][25] although different nanotherapies have been developed for targeted treatment of IBD. On the other hand, patient-friendly oral delivery is highly preferred for treatment of gastrointestinal and chronic diseases, owing to its convenience, high patient compliance, desirable cost-effectiveness, and good safety profile.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] A recent study revealed the potential of Ac2-26 for the treatment of colitis after intraperitoneal or intramucosal injection of Ac2-26 in nanoparticles (NPs). [16][17][18][19][20][21] However, there are still tremendous challenges in the design and development of translational nanovehicles for oral delivery of macromolecular therapeutics, [16,[22][23][24][25] although different nanotherapies have been developed for targeted treatment of IBD. On the other hand, patient-friendly oral delivery is highly preferred for treatment of gastrointestinal and chronic diseases, owing to its convenience, high patient compliance, desirable cost-effectiveness, and good safety profile.…”
Section: Introductionmentioning
confidence: 99%
“…YGPs were labeled with FITC according to the previous study. [ 39 ] Briefly, 1 g of YGPs were incubated in 100 mL of sodium carbonate buffer solution (0.1 m , pH 9.2) for 0.5 h, and FITC dissolved in DMSO (1 mg mL −1 ) was added dropwise with stirring overnight in the dark. Finally, the FITC‐labeled YGPs (denoted as YGPs‐FITC) were collected by centrifugation, and washed well with sterile water, followed by lyophilization.…”
Section: Methodsmentioning
confidence: 99%
“…These chitosan-bound particles were more readily transcytosed by M cells, via the ganglioside GM1 receptor. Another example of exploiting the endogenous role of Mcells is the use of yeast capsules containing nanoparticles [95]. Firstly, there are a very limited number of Peyer's patches in the human gut [89] and the total number of M cells on the intestinal surface is estimated at only one millionth the number compared to other epithelial cells [96].…”
Section: M-cell-mediated Transcytosismentioning
confidence: 99%